Bureaucracy's Responsibility in Public Services (Study of the Regional Disaster Management Agency (BPBD) of Kupang Regency) - Yane Kristiana LALAN; William DJANI; Maria Magadalena LINO (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the responsiveness of bureaucracy in public services at the Regional Disaster Management Agency (BPBD) of Kupang Regency, especially in responding to community needs during and after a disaster. The primary concern raised is the extent to which BPBD is able to provide services that meet community expectations in emergencies and identify the factors that support and inhibit this. This study employs a qualitative approach, utilizing a case study method. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation studies. Informants were selected purposively, consisting of BPBD officials and residents affected by the disaster. The study focuses on three main aspects: response-ability (officer understanding and clarity of communication), speed of service (utilization of time and technology), and accuracy of service (suitability of services and procedures). The results of the study indicate that flooding is the most dominant and broad-impact event in the study area. Flat topographic factors, infrastructure damage, and inadequate drainage systems cause the vulnerability of this area. Field findings indicate that three main aspects influence the responsiveness of the Kupang Regency BPBD in handling flood disasters: the aspect of response-ability identified limitations in technical understanding among officers due to their low disaster education background and a minimal training budget.